SAT0198 Relation of Doppler Ultrasound Synovitis versus Clinical Synovitis with Changes in Native Complement Component Levels in Rheumatoid Arthritis Patients Treated with Biologic Disease-Modifying Antirheumatic Drugs. (10th June 2014) - Montoro Alvarez, M.; Yew Chong, O.; Janta, I.; Serrano, B.; Mata, C.; Martinez, L.; Martinez-Barrio, J.; Hinojosa, M.; Bello, N.; Ovalles, J.; Nieto, J.; Valor, L.; et al.
Abstract : Background: The complement system not only forms part of the innate immunity but also contribute in modulating the adaptive responses [1]. There are evidence suggesting increased level of complement as acute phase reactant mediated by proinflammatory cytokines important in active rheumatoid arthritis (RA) such as interleukin 1 (IL-1), interleukin 6 (IL-6) and tumour necrosis factor-α (TNF-α) [2-5]. Activation of the complement system, by immune complexes or C-reactive protein (CRP), plays an important role in inflammatory activity of RA as shown by significant level of complement degradation products found in the synovial fluid of affected joints in RA [6, 7]. Objectives: The complement system plays a fundamental role in mediating the activity of rheumatoid arthritis (RA). Biologic therapy can reduce native complement component levels and its activation. We aimed to study the relation of Doppler ultrasound (US) synovitis versus clinical synovitis with changes in native complement component levels in RA patients on biologic therapy. Methods: This was a prospective cross-sectional study. Ninety seven consecutive patients with RA on biologic therapy for at least 3 months were recruited. Clinical, laboratory and Doppler US assessments were performed. The Disease Activity Score in 28 joints (DAS28), Simplified Disease Activity Index (SDAI) and a 12-joint US assessment were carried out. Synovitis was semiquantitatively scored in B-mode and power Doppler (PD) mode. Results: A significant decrease in native complement (i.e. C3 and C4) and C-reactive protein (CRP) levels was observed. This was highly significant for C3 decrease (p<0.0005), and C4 decrease (p<0.0005). Synovitis detected by PD US showed significant negative association with C3 change (p<0.008), where patients with higher C3 change were more likely to have PD US inactive status on assessment. Correlations between complement levels, CRP levels and their changes with clinical and PD US disease activity. Conclusions: Our results suggested that disease inactive status determined by PD US but not by clinical assessment can be related with decrease in complement in RA patients treated with biologic therapy. References: Morgan BP et al. Immunol Lett 2005; 97: 171-9. Miura N et al. J Biol Chem 1987; 262: 7298-305. Andus T et al. Eur J Immunol 1988; 17: 1193-7. Anthony R et al. Eur J Immunol 1989; 19: 1405-12. Ramadori G et al. Eur J Immunol 1988; 18: 1259-64. Kemp PA et al. J Clin Lab Immunol 1992; 37: 147-62. Westedt ML et al. J Rheumatol 1985:12;449-55. Disclosure of Interest: M. Montoro Alvarez: None declared, O. Yew Chong: None declared, I. Janta: None declared, B. Serrano: None declared, C. Mata: None declared, L. Martinez: None declared, J. Martinez-Barrio: None declared, M. Hinojosa: None declared, N. Bello: None declared, J. Ovalles: None declared, J. Nieto: None declared, L. Valor: None declared, F. Lopez-Longo: None declared, I. Monteagudo Consultant for: Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, MSD and Esaote, C. Gonzalez: None declared, J. Garrido: None declared, A. Rosman: None declared, L. Ing Soo: None declared, E. Naredo Grant/research support: Grant/research support: UCB and MSD Consultant for: Abbvie, Roche Farma, Bristol-Myers Squibb, Pfizer, UCB, General Electric Healthcare, and Esaote, L. Carreño: None declared DOI: 10.1136/annrheumdis-2014-eular.4379